Phylogenetics and evolution of Digitaria grasses, including cereal crops fonio, raishan, and Polish millet - Burton,GP; Ceci,P; MacKinnon,L; Masters,LE; Randrianarimanana,NFH; Ryan,P; Turnbull,C; Ulian,T; Vorontsova,MS (Annals of Botany, 2026)
Background and Aims Millet crops in the grass genus Digitaria include white and black fonio (D. exilis and D. iburua), raishan (D. compacta) and Polish millet (D. sanguinalis), cultivated across West Africa, India, and Europe. Fonio and raishan crops are important to supporting food security and subsistence agricultural systems in rural communities, while D. sanguinalis is no longer cultivated. These crops are resilient to challenging climates. We aim to produce an integrated study of these crops: a phylogeny of the Digitaria genus including all four food species, to identify key crop wild relatives (CWRs); time-calibrated biogeographic analysis, to investigate the history and evolution of Digitaria; and morphological study to assess the transition between wild and domesticated species. Methods We use the Angiosperm 353 target-enrichment sequencing approach to produce maximum likelihood and coalescent model nuclear phylogenies for 46 Digitaria species, and Bayesian methods to propose an evolutionary and biogeographic history for the genus. Morphology of wild and cultivated species is investigated for spikelets and growth habits using microscopy and SEM imaging.Key Results Four distinct evolutionary lineages are found for the Digitaria crops, and we identify new close crop wild relatives D. fuscescens, D. atrofusca, D. setigera and D. radicosa, and D. ciliaris. South and eastern Africa is proposed as a likely origin of early Digitaria divergence, with crop lineages diverging from wild relatives around 2-6mya. Incomplete domestication traits are observed, including the loss of trichomes, but no clear change in appearance for spikelet or abscission zone morphologies.Conclusions The knowledge produced in this study about Digitaria CWRs will be useful in improving crop traits through targeted breeding and physiological studies; and we also highlight the need for conservation of seed material through programmes working with local partners, for these important climate-tole